Notch Signalling in the Hippocampus of Patients With Motor Neuron Disease - Gómez-Pinedo, Ulises; Galán, Lucía; Matías-Guiu, Jordi A.; Pytel, Vanesa; Moreno, Teresa; Guerrero-Sola, Antonio; Matías-Guiu, Jorge (Frontiers in Neuroscience, 2019)
Introduction The Notch signalling pathway regulates neuronal survival. It has some similarities with the APP signalling pathway, and competes with the latter for α- and γ-secretase proteolytic complexes. The objective of this study was to study the Notch signalling pathway in the hippocampi of patients with motor neuron disease. Methods We studied biological material from the autopsies of 12 patients with motor neuron disease and 4 controls. We analysed the molecular markers of the Notch and APP signalling pathways, TDP43, tau, and markers of neurogenesis. Results and Conclusion Low NICD expression suggests Notch signalling pathway inactivation in neurons. Inactivation of the pathway despite increased Notch1 expression is associated with a lack of α-secretase expression. We observed increased β-secretase expression associated with activation of the amyloid cascade of APP, leading to increases in amyloid-β and AICD peptides and decreased levels of Fe65. Inactivation of the Notch signalling pathway is an important factor in decreased neurogenic response in the hippocampi of patients with amyotrophic lateral sclerosis.